Macroeconomics for managers - "Evans, Michael K." (Oxford, 2004)
This text offers business school students an excellent practical explanation of the short-term linkages in the macroeconomic arena. While the underlying theoretical constructs are not ignored, emphasis is placed on the empirical underpinnings and managerial implications of macroeconomics. The text begins by introducing key concepts such as the GDP, National and Personal Income, and the various measures of inflation and unemployment. Building on this foundation it then analyzes the following aspects of macroeconomics: aggregate supply and demand, international financial markets, cyclical fluctuations, policy analysis, and forecasting.
Keywords: Macroeconomics